2016
DOI: 10.3389/fpsyg.2016.01190
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Investigation of Behavioral Contagion in Common Marmosets (Callithrix jacchus): Indications for Contagious Scent-Marking

Abstract: Behavioral contagion is suggested to promote group coordination that may facilitate activity transitions, increased vigilance, and state matching. Apart from contagious yawning, however, very little attention has been given to this phenomenon, and studies on contagious yawning in primates have so far only focused on Old World monkeys and apes. Here we studied behavioral contagion in common marmosets, a species for which group coordination and vigilance are paramount. In particular, we investigated the contagio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 80 publications
1
34
0
1
Order By: Relevance
“…We here discuss the consequences of our findings for the different proximate and ultimate hypotheses that currently exist. CY has thus far been observed in highly social species 6,7,15,17,[19][20][21][22] (but see: 1,[24][25][26][27] ). Orangutans have meaningful social interactions that occur more often than is expected by chance alone 76 , but these interactions occur at a much lower frequency compared to bonobos and chimpanzees 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…We here discuss the consequences of our findings for the different proximate and ultimate hypotheses that currently exist. CY has thus far been observed in highly social species 6,7,15,17,[19][20][21][22] (but see: 1,[24][25][26][27] ). Orangutans have meaningful social interactions that occur more often than is expected by chance alone 76 , but these interactions occur at a much lower frequency compared to bonobos and chimpanzees 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Like other primates, marmosets mostly rely on vocalizations (Miller and Wang, 2006 ; Chen et al, 2009 ; Miller et al, 2010 ; Watson and Caldwell, 2010 ; Bakker et al, 2014 ; Kato et al, 2014 ; Agamaite et al, 2015 ) and visual cues (de Boer et al, 2013 ; Massen et al, 2016 ) for their communication, although social grooming (Lazaro-Perea et al, 2004 ) and scent marking (Epple, 1970 ; Massen et al, 2016 ) are present as well. Since ASDs are characterized by gaze avoidance, it is particularly interesting that marmosets are able to use a variety of facial expressions for communication (Kemp and Kaplan, 2013 ) and to gain information by geometrical gaze following, even from human experimenters (Burkart and Heschl, 2006 ).…”
Section: From Mice To Menmentioning
confidence: 99%
“…Other indices that could have been influenced by context are Scent marking F and Monitoring P . Scent marking F , which did not have a salient loading on any component in our study, has been suggested to be a contagious behaviour in marmosets (Massen et al, 2016) and so it is not possible to determine whether this behaviour was spontaneous, or triggered by the behaviour of others. Moreover, scent marking might have several functions (Roberts, 2012) and might be affected by sex (French and Cleveland, 1984) or breeding position (Heistermann et al, 1989).…”
Section: Repeatability Of Behavioursmentioning
confidence: 65%